A 3D Hellenic archaeological cadastre based on LADM - Γόγολου, Χριστίνα (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Αγρονόμων και Τοπογράφων Μηχανικών, 2016)
Greece is a country that claims a significant cultural heritage that affected the evolution of many cultures and has set the cornerstone for the development of the western societies. As a crossroad of ideas due to its geographical position, Greece has always been a place of creation. This has given marvelous examples of history, architecture, art, philosophy and so on. The Greek State, since its establishment, has a strict legal framework which reflects the importance of the conservation of ancient treasures. Over the years, various public services have been responsible for the protection of different types of culture; movable, immovable and tangible heritage are the three classifications described in the legal framework for the protection of cultural assets. Regarding the management tools, there is a plethora of registries implemented for the administration of national cultural assets, such as the National Monuments Archive and the Constant Catalogue for Declared Archaeological Sites and Monuments. Today, the Hellenic Archaeological Cadastre is an ongoing project for the registration of the ownership status of the immovable archaeological assets with a cadastral approach. The project aims to the development of a modern registry for properties with archaeological an architectural features. Land Administration is an international good practice followed by public institutions and other organizations for the identification and management of people-to-land-relationships. Land Administration is expressed in the various systems developed around the world for terrestrial and marine territories. In this context, infrastructure for the administration of issues related to the land with spatial reference has been implemented. Spatial Data Infrastructure for specific spatial components provide institutions with valuable management tools, such as Land and Marine Administration Systems, cadastral systems, coastal management registries and environmental assessment tools. Standardization in Land Administration has also raised as a necessity to the implementation of spatial management systems. Standards are widely used today for the formation of conceptual models and software architecture as they provide possibilities for common development, expression of shared terminology to the systems and compatibility with global structures. Last but not least, standards have enabled the interoperability between different systems, leading to feasible forms of databases and communication between various organizations. The main purpose of this Master Thesis is the adjustment of the LADM in the basic conceptual schema of the Hellenic Archaeological Cadastre, for the development of a three-dimensional system with extension to marine regions. A second goal is set to the research; the identification of the legal, jurisdictional and technical requirements that are necessary for the three-dimensional spatial representation of archaeological cadastral data in properties with archaeological interest as well as in marine archaeological sites in Greece. For the above aims, the research comprises two phases. The first phase includes the analysis of a theoretical background in Land Administration. This combines an attempt to provide the State of the Art in Land Administration Systems, Spatial Data Infrastructures marine and coastal administration systems as well as the investigation of the standardization process, together with an explicit description of the concepts and attributes of the Land Administration Domain Model. The field of 3D Cadastres and the barriers and legal constraints for the definition of 3D property objects are also investigated. At last, a review of the State of the Art in the management of the cultural heritage and a description of efforts for the implementation of cultural property protection systems on a national and international scale are also included. The second phase aims to the conceptualization of a three-dimensional Hellenic Archaeological Cadastre based on the LADM. A conceptual model that adopts the codification proposed by the core model of the LADM in the complex task of classification of data for the archaeological space of Greece is described in detail. Classes and their attributes, together with codelists for the various types are explicitly presented. Explanations and external classes necessary to the system due to the multiplicity of the Greek archaeological environment are also added to the proposed model. At last, an extensive report to the various legal, organizational and technical reforms that need to be realized on a national scale in order to determine the premises for the assignment of 3D property objects on an Archaeological Cadastre are provided. Several stimulating conclusions for the three-dimensional and marine archaeological cadastral registrations and for the interoperability of systems arise from the description of the developed model, which are extensively presented in the final part of this second phase.